2003
DOI: 10.1103/physrevd.67.114024
|View full text |Cite
|
Sign up to set email alerts
|

Testing anomalous gauge couplings of the Higgs boson via weak-boson scatterings at the CERN LHC

Abstract: We propose a sensitive way to test the anomalous HV V couplings (V = W ± , Z 0 ) of the Higgs boson (H), which can arise from either the dimension-3 effective operator in a nonlinearly realized Higgs sector or the dimension-6 effective operators in a linearly realized Higgs sector, via studying the V V scattering processes at the CERN LHC. The gold-plated pure leptonic decay modes of the final state weak bosons in the processes pp → V V jj are studied. For comparison, we also analyze the constraints from the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
3
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 64 publications
0
52
3
4
Order By: Relevance
“…For example, O BW and O Φ,1 are related to the oblique correction parameters S and T , and are thus strongly constrained by the precision EW data. The 2σ constraints on |f BW /Λ 2 | and |f Φ,1 /Λ 2 | are: [20]. The operators O Φ,2 and O Φ,3 are related to the triple and quartic Higgs boson self-interactions, and have been studied in detail in Ref.…”
Section: B Anomalous Gauge Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, O BW and O Φ,1 are related to the oblique correction parameters S and T , and are thus strongly constrained by the precision EW data. The 2σ constraints on |f BW /Λ 2 | and |f Φ,1 /Λ 2 | are: [20]. The operators O Φ,2 and O Φ,3 are related to the triple and quartic Higgs boson self-interactions, and have been studied in detail in Ref.…”
Section: B Anomalous Gauge Couplingsmentioning
confidence: 99%
“…[20], in which the effective couplings for a single-Higgs system, and the pure leptonic decay mode of the final state W bosons was considered. It showed that the required integrated luminosity was high.…”
Section: General Features Of Studying the Lhc Signatures Of Hmentioning
confidence: 99%
“…(3.6) comes form the normalization of the Higgs boson kinetic term which gets modified due to higher dimensional operators. The constraints coming from the electroweak precision data are [17], …”
Section: Jhep12(2013)077mentioning
confidence: 99%
“…The deviations of Higgs couplings are encoded in the higher dimensional effective Lagrangian coefficients including their renormal ization group flow at the loop level [35][36][37][38][39][40][55][56][57][58][59][60], Due to the presence of such higher dimensional oper ators, perturbative unitarity of the scattering amplitudes is violated at a certain high energy scale (cutoff scale of the effective theory) in the effective field theory [64,65], Yet unknown UV completion theory therefore needs to replace the effective field theory above the cutoff scale. In this sense, in addition to the studies of the effective field theory, we need to study UV completions model dependently.…”
Section: Introductionmentioning
confidence: 99%